PERAN KETEPATAN PENEMPATAN KERJA TERHADAP KINERJA KARYAWAN (Studi Pada Karyawan Bagian Produksi PT. Otsuka Indonesia) (Jurnal Bisnis Indonesia, 2022)
PT. Otsuka Indonesia, which is a well-known manufacturer of infusion fluids in Indonesia and has an established organizational structure, becomes an attraction for research on work placements and employee performance. This theme is important considering that a good job placement for its employees will have an impact on improving the overall performance of employees in a large scope of the company. This study aims to analyze and explain the effect of work placement on employee performance. Researchers used descriptive and associative approaches as the basis for the form of writing. The population in this study were 87 people who are employees of the production department at PT. Otsuka Indonesia, where they are one of the company's main components in production, and set all 87 respondents as saturated samples. The results showed that the hypothesis had a significant effect, namely job placement on employee performance. Employees consider that they have worked in accordance with the field of education they have, work based on knowledge to be able to analyze and identify a job, and the demands of the field of work have trained employees' skills in working by relying on stamina, level of focus, and thoroughness. The five aspects of employee performance which include discipline, high dedication, quantity of work, reliability, and attitude are also assessed by employees of the production division of PT Otsuka Indonesia as being fulfilled when they carry out their duties.  DOI : https://doi.org/10.33005/jbi.v13i1.3081